2018
DOI: 10.1016/j.cell.2018.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Hair Cell Mechanotransduction Regulates Spontaneous Activity and Spiral Ganglion Subtype Specification in the Auditory System

Abstract: Type I spiral ganglion neurons (SGNs) transmit sound information from cochlear hair cells to the CNS. Using transcriptome analysis of thousands of single neurons, we demonstrate that murine type I SGNs consist of subclasses that are defined by the expression of subsets of transcription factors, cell adhesion molecules, ion channels, and neurotransmitter receptors. Subtype specification is initiated prior to the onset of hearing during the time period when auditory circuits mature. Gene mutations linked to deaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
337
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(374 citation statements)
references
References 97 publications
20
337
1
3
Order By: Relevance
“…It demonstrated that new SGNs were present in all the samples of experimental groups. In addition, we checked other SGN genes such as Calb2, Pou4f1, Lypd1, Slc17a6, Slc17a7, and Pvalb , which have recently been reported in different SGN single‐cell RNA‐Seq studies . Samples #4 and #9 showed enhanced expression of all of these SGN genes compared to other samples (red arrows in Figure D).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…It demonstrated that new SGNs were present in all the samples of experimental groups. In addition, we checked other SGN genes such as Calb2, Pou4f1, Lypd1, Slc17a6, Slc17a7, and Pvalb , which have recently been reported in different SGN single‐cell RNA‐Seq studies . Samples #4 and #9 showed enhanced expression of all of these SGN genes compared to other samples (red arrows in Figure D).…”
Section: Resultsmentioning
confidence: 89%
“…The OHCs detect and amplify sound; this subsequently leads to the activation of IHCs, which in turn convert sound into electrical signals . Approximately 95% of spiral ganglion neuron (SGNs) are type I SGNs, which can be further subdivided into three subtypes: Type I‐A, Type I‐B, and Type I‐C, and the remaining 5% of SGNs are type II SGNs, as supported by both morphological and single‐cell transcriptome analysis . IHCs are the primary sensory cells that are connected to myelinated type I SGNs, while OHCs are innervated by unmyelinated type II SGNs.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…; Sun et al . ). As explained above, such a compensatory mechanism is unlikely in Otof KOs, due to reduced spontaneous activity rates at P11 and P30.…”
Section: Discussionmentioning
confidence: 97%
“…Shear stress is elicited by the flow of blood and interstitial fluid around cancer cells. To produce transient cellular responses, mechanical stresses are sensed and transduced to generate biochemical signals via a process called mechanotransduction . This process involves mechanosensors (e.g.…”
Section: Mechanical Stressmentioning
confidence: 99%